ANXA11 biomolecular condensates facilitate protein-lipid phase coupling on lysosomal membranes - Jonathon Nixon-Abell; Francesco S. Ruggeri; Seema Qamar; Therese W. Herling; Magdalena A. Czekalska; Yi Shen; Guozhen Wang; Christopher King; Michael S. Fernandopulle; Tomas Sneideris; Joseph L. Watson; Visakh V. S. Pillai; et al. (Nature Communications)
Abstract Phase transitions of cellular proteins and lipids play a key role in governing the organisation and coordination of intracellular biology. Recent work has raised the intriguing prospect that phase transitions in proteins and lipids can be co-regulated. Here we investigate this possibility in the ribonucleoprotein (RNP) granule-ANXA11-lysosome ensemble, where ANXA11 tethers RNP granules to lysosomal membranes to enable their co-trafficking. We show that changes to the protein phase state within this system, driven by the low complexity ANXA11 N-terminus, induces a coupled phase state change in the lipids of the underlying membrane. We identify the ANXA11 interacting proteins ALG2 and CALC as potent regulators of ANXA11-based phase coupling and demonstrate their influence on the nanomechanical properties of the ANXA11-lysosome ensemble and its capacity to engage RNP granules. The phenomenon of protein-lipid phase coupling we observe within this system serves as a potential regulatory mechanism in RNA trafficking and offers an important template to understand other examples across the cell whereby biomolecular condensates closely juxtapose organellar membranes.